In Silico Evaluation of (3R,4R)-Piperidine-Pyrrolopyrimidine Derivatives as Potential Anticancer Agents Targeting Topoisomerase I/II, Bcl-2, and HDAC2 - Haresh Ram; Jyotindra Bhatt; Ranjit Pada (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The development of novel anticancer therapeutics is a critical and ongoing challenge in medicinal chemistry. Heterocyclic scaffolds such as pyrrolo[2,3-d]pyrimidines and piperidine-based structures have demonstrated remarkable activity across various biological targets, particularly in oncology. This study investigates a series of (3R,4R)-piperidine-pyrrolopyrimidine derivatives through comprehensive in silico methodologies. Targeting Topoisomerase I, Topoisomerase II, Bcl-2, and HDAC2—key proteins in cancer progression and survival—we employed molecular docking, MM-GBSA binding free energy calculations, and quantitative structure–activity relationship (QSAR) modeling. The pharmacokinetic and toxicological properties were predicted using SwissADME, pkCSM, and ProTox-II platforms. Results revealed favorable binding affinities, stable molecular interactions, and acceptable drug-like behavior. The findings support the potential of these compounds as lead candidates for future anticancer development.